DISEMINASI INFORMASI DALAM PENERIMAAN SISWA BARU BERBASIS ANDROID PADA SMA NEGERI ABUNG TINGGI LAMPUNG UTARA - Novrianto, Novrianto; Sumarsono, Sumarsono; Indrianingsih, Yuliani (Compiler, 2013)
Information regarding the admission of new students in a school is very important to support the smooth reception o f new students. Good information distribution process, will improve the quality of education in a school. Application o f these new students is a solution that can parents help their parents in distributing information about the graduation o f their students in a school. The application supports the announcement o f the distribution process before the announcement o f new admissions at the school run. This application was developed using Java programming language, assisted by Net.bin for Android Operating System environment. This method is based on client-server, where mobile devices like cell phones or netbooks as a web server as a client and server. Parents are parents who have Android-based mobile devices, can use this application to support the admission o f new students. Android mobile applications can make it easier for parents to see the announcement o f new admissions, thereby saving time getting to know their students are accepted or not on SMA High Abung, North Lampung.